The Role of ICT and Human Capital Development in Pursuing a Demographic Dividend and Improving Economic Welfare in Indonesia - Nurarifin; Sedwivia Ridena (The Journal of Indonesia Sustainable Development Planning, 2020)
This article aims to provide evidence that Information and Communication Technology (ICT) and human development play an important role in pursuing a demographic dividend and accelerating economic welfare in Indonesia by exploiting provincial data from 2012 to 2017. The empirical evidence implemented in this research is Two-Stage Least Squares and dynamic system Generalized Method of Moments (GMM) techniques. The results show that a 1%-point rise in ICT development growth potentially leads to an approximately 0.24%-point increase in economic welfare growth, whereas an in life expectancy may decrease GDP per capita. The analysis also finds that a 1%-point increase in the ratio of the participation rate will promote a nearly 0.16%-point rise in per capita output. Meanwhile, a 1%-point increase in the share of the working-age population will generate roughly 0.19%-point rise in per capita income. A recent paper suggests that policymakers have to promote more supportive ICT and human development policies to pursue a demographic dividend since even though they have a positive impact on per capita income, the magnitude remains relatively low.